Association of Hyperchloremia and Acute Kidney Injury in Patients With Traumatic Brain Injury. (January 2022) - Yamane, David P.; Maghami, Sam; Graham, Ada; Vaziri, Khashayar; Davison, Danielle
Introduction: Hypertonic saline is often used to treat patients with traumatic brain injury. It carries the undesired side effect of hyperchloremia, which has been linked to acute kidney injury (AKI). We sought to evaluate the relationship of hyperchloremia and AKI in this population and whether the absolute exposure to hyperchloremia, including maximal hyperchloremia and duration of hyperchloremia were associated with AKI. Methods: A retrospective study of severe traumatic brain injury patients who received hypertonic saline at a single academic institution. Demographics, head abbreviated injury scale, development of hyperchloremia (Cl ≥ 115), duration of hyperchloremia, highest chloride level, duration of hypertonic saline use, admission GFR, and administration of nephrotoxic medications were abstracted. The outcome of interest was the association between renal function and hyperchloremia. Results: A total of 123 patients were included in the study. Multivariable logistic regression analysis demonstrated that only duration of hyperchloremia ( p = 0.014) and GFR on admission ( p = 0.004) were independently associated with development of AKI. The number of days of hypertonic saline infusion ( p = 0.79) without the persistence of hyperchloremia and highest serum chloride levels ( p = 0.23) were not predictive of AKI development. Discussion: In patients with traumatic brain injury, admission GFR and prolonged hyperchloremia rather than the highest chloride level or the duration of hypertonic saline infusion were associated with the development of AKI.